Cespitulones A and B, Cytotoxic Diterpenoids of a New Structure Class from the Soft Coral Cespitularia taeniata - Yu-Chi Lin; Shih-Sheng Wang; Chung-Hsiung Chen; Yao-Haur Kuo; Ya-Ching Shen (Marine Drugs, 2014)
Two novel diterpenoids, cespitulones A (1) and B (2), were isolated from extracts of the soft coral Cespitularia taeniata. Both compounds possess an unprecedented bicyclo [10.3.1] ring system with C-C bond connections between C-10 and C-20, and between C-20 and C-11. Their structures were elucidated on the basis of extensive spectroscopic analyses. Compound 1 exhibited significant cytotoxicity against human medulloblastoma and colon adenocarcinoma cancer cells.